Karol Szymanowski's Music in the Perception and Creative Activities of Children at the Stage of Early Education - Rafał Majzner (Maria Curie-Skłodowska University, Lublin, Poland, 2019)
The creative activity of children at pre-school and early-school age can take various forms and be evoked by means of specific measures. Music is considered one of the factors stimulating the imagination, and thus inspiring the creativity of children. The article presents the results of research on the children's perception of Karol Szymanowski's music. It analyzes their works of art and expression inspired by the composer's selected works. The nalysis lead to the conclusion that children are open to musical experiences involving classical music, and are eager to undertake creative activities based on listened music.